Unmasking a fungal fire. - Ivy M Dambuza; Adilia Warris; Fabián Salazar (PLoS Pathogens)
Immune checkpoint inhibitor (ICI) therapy represents a breakthrough cancer treatment by stimulating dysfunctional T cells in the tumour environment to kill cancer cells. Beyond effects on anticancer immunity, ICI therapy may be associated with increased susceptibility to or more rapid resolution of chronic infections, particularly those caused by human fungal pathogens. In this concise review, we summarise recent observations and findings that implicate immune checkpoint blockade in fungal infection outcomes.